Penerapan Algoritma Regresi Linier Berganda Untuk Memprediksi Hasil panen Padi Di Kota Pagar Alam - Dedi Setiadi; S Sasmita; Melza Yolanda (LPPM STIKOM Tunas Bangsa, 2024)
Many farmers experience crop failure. Apart from that, farmers do not know what factors most influence the crop yield, so farmers cannot anticipate crop failure. Based on these conditions, a prediction model is needed that is able to predict rice crop yields so that farmers can find out the causes of crop failure, the factors that most influence crop yields and make better estimates of what will happen in the future, so that farmers can make policies and measures to anticipate crop failure in the next planting. This research aims to predict rice harvest yields in Pagar Alam City so as to help farmers predict rice harvest more easily, farmers can take policies and actions to predict crop failure using a multiple linear regression algorithm. Development method. The system used is the waterfall method and testing using black box testing. The rice harvest prediction system is an innovative solution that aims to accurately estimate rice harvest yields in Pagar Alam City.